A Novel Homozygous Non-sense Mutation in the Catalytic Domain of MTHFR Causes Severe 5,10-Methylenetetrahydrofolate Reductase Deficiency - Massadeh, Salam; Umair, Muhammad; Alaamery, Manal; Alfadhel, Majid (Frontiers in Neurology, 2019)
Background: Severe 5,10-methylenetetrahydrofolate reductase (MTHFR) deficiency is a heterogeneous metabolic disorder inherited in an autosomal recessive manner. Pathogenic mutations in MTHFR gene have been associated with severe MTHFR deficiency. The clinical presentation of MTHFR deficiency is highly variable and associated with several neurological anomalies. Methods: Direct whole-exome sequencing (WES) was performed in all the five available individuals from the family, including the affected individual (III-7) using standard procedures. Results: We observed a proband (III-7) with an abnormality in the cerebral white matter, apnoea, and microcephaly. WES analysis identified a novel homozygous nonsense mutation (c.154C>T; p.Arg52*) in MTHFR gene that segregated with the disease phenotype within the family. Conclusion: We identified a novel nonsense mutation in MTHFR gene in a single Egyptian family with severe MTHFR deficiency. The present investigation is clinically important, as it adds to the growing list of MTHFR mutations, which might help in genetic counselling of families of affected children and proper genotype-phenotype correlation. Keywords: MTHFR, nonsense mutation, white matter disease, microcephaly, severe methylenetetrahydrofolate reductase deficiency.